PENGARUH PENGGUNAAN MEDIA SCRAPBOOK TERHADAP MOTIVASI BELAJAR IPS KELAS IV SDN - Alpia; Rury Rizhardi; Ida Suryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Media scrapbook which packaged in book form by combining various pieces of images as well as explanations that are expected to attract the attention and activity of students This study aims to determine whether there is an influence of the use of scrapbook media on the motivation to learn social studies grade IV SD Negeri 22 Palembang. This research design is a pre-experimental research with the design of The One Group Pretest-Posttest design. The population of this study was the entire class IV of SDN 22 Palembang which amounted to 24 people. The sample is determined by random sampling technique. The sample of this study was students conducted using test methods in the form of multiple choice and questionnaires measuring learning motivation. The results showed that there was an influence of the use of scrapbook media on the motivation to learn social studies SDN 22 Palembang. This is shown from the paired test results of the T-test sample, pretest data and posttest learning motivation get a signification value of 0.819 < 0.005, then Ho is rejected and Ha is accepted. Keywords: Media, Scrapbook, Learning motivation